2015
DOI: 10.1007/s10654-015-0065-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitor antidepressant use in first trimester pregnancy and risk of specific congenital anomalies: a European register-based study

Abstract: Dolk, H. (2015). Selective serotonin reuptake inhibitor antidepressant use in first trimester pregnancy and risk of specific congenital anomalies: a European register-based study. European Journal of Epidemiology, 30(11), 1187-1198. https://doi.org/10.1007/s10654-015-0065-y General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 84 publications
6
58
0
4
Order By: Relevance
“…Among 27 articles that were selected for review, no consistent pattern has been observed in the reported risk of CHA. A slight increase in risk was found, particularly for paroxetine, in a number of studies in various countries (see Table S1) [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], but a number of other studies reported no increased risk (see Table S2) [23,24,25,26,27,28,29,30,31,32]. The dose of SRIs may also be an important determinant of the risk.…”
Section: The Risk Of Congenital Heart Anomalies (Cha) Associated Wmentioning
confidence: 99%
“…Among 27 articles that were selected for review, no consistent pattern has been observed in the reported risk of CHA. A slight increase in risk was found, particularly for paroxetine, in a number of studies in various countries (see Table S1) [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], but a number of other studies reported no increased risk (see Table S2) [23,24,25,26,27,28,29,30,31,32]. The dose of SRIs may also be an important determinant of the risk.…”
Section: The Risk Of Congenital Heart Anomalies (Cha) Associated Wmentioning
confidence: 99%
“…However, the literature offers no consistency: paroxetine is implicated in some studies[24],[25], and fluoxetine[24,26,27], citalopram/ escitalopram[17,27] and sertraline[17,28] in others. Meta-analyses[26,29,30] and analysis of 12 EUROCAT registries[31] indicate an overall association between SSRI exposure and congenital heart defects (CHD); however, there is no consensus[21,22,29,32,33]. The most persistent associations relate to paroxetine exposure and CHD[22,24,27,30,31], particularly at doses >25mg/day[34].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses[26,29,30] and analysis of 12 EUROCAT registries[31] indicate an overall association between SSRI exposure and congenital heart defects (CHD); however, there is no consensus[21,22,29,32,33]. The most persistent associations relate to paroxetine exposure and CHD[22,24,27,30,31], particularly at doses >25mg/day[34]. Epidemiologists also report increased risks of: neural tube defects[33,35], ano-rectal stenosis/ atresia[23], gastroschisis, omphalocele[35], renal dysplasia, hypospadias[27], limb reduction[23], talipes equinovarus (clubfoot)[23], craniosynostosis[35], anomalies of the eye[18], ear, face[36], respiratory[36] and digestive tracts[15,24].…”
Section: Introductionmentioning
confidence: 99%
“…EUROCAT har gjennomført studier både når det gjelder forholdet mellom miljøfaktorer og misdannelser, for eksempel sammenhengen mellom Tsjernobylulykken og misdannelser (der man konkluderte med manglende sammenheng (24)), mellom mors sykdommer som diabetes og misdannelser (14) og mellom legemiddelbruk i svangerskapet og misdannelser (25)(26)(27)(29)(30). Sistnevnte studier har også blitt videreført i et eget forskningsprosjekt der man koblet EUROCATdata med andre databaser som hadde opplysninger om legemiddelbruk i svangerskapet, EUROmediCAT (28).…”
Section: åRsaker Til Medfødte Misdannelserunclassified
“…I Norge ble MFR koblet med Nasjonalt reseptbasert legemiddelregister (Reseptregisteret). Gjennom EUROCAT og EUROmediCAT er sammenhengen mellom flere typer legemidler og medfødte misdannelser evaluert, for eksempel forskjellige typer antiepileptika (25,26,29,30), SSRI (27,31), antiastmatika (32) og flere.…”
Section: åRsaker Til Medfødte Misdannelserunclassified